Design and Analysis of a Stand-Alone PV System for a Rural House in Pakistan - Amjad Iqbal; M. Tariq Iqbal (International Journal of Photoenergy)
In this paper, thermal modeling of a typical rural house in Pakistan has been done using BEopt, to determine the hourly load profile. Using the load data, the design of a stand-alone PV system has been completed using HOMER Pro. The designed system consists of a 5.8 kW PV with eight batteries of 12 V, 255 Ah, and a 1.4 kW inverter. The system analyses show that such system can support mainly lighting and appliance load in a rural house. The dynamic model of the designed system has been simulated in MATLAB-Simulink. Perturbation and observation-based algorithm has been used for maximum power extraction from PV. Simulation results indicate that the system can provide a stable voltage and frequency for the domestic load. The method and analysis presented here can be used for the PV system design for other parts of the world.